7
$\begingroup$

Find $x\in \Bbb Z$ such that $x=\sqrt[3]{2+\sqrt{5}}+\sqrt[3]{2-\sqrt{5}}$

Tried (without sucess) two different approaches: (a) finding $x^3$ by raising the right expression to power 3, but was not able to find something useful in the result that simplifies to an integer; (b) tried to find $a$ and $b$ such that $(a+\sqrt{b})^3=2+\sqrt{5}$ without success.

The answer stated for the problem in the original source (a local Math Olympiad Constest) is $x=1$.

$\endgroup$
8
$\begingroup$

$$x=\sqrt[3]{2+\sqrt{5}}+\sqrt[3]{2-\sqrt{5}}\\x^3=2+\sqrt5+2-\sqrt5+3\sqrt[3]{2+\sqrt{5}}\cdot\sqrt[3]{2-\sqrt{5}}(\sqrt[3]{2+\sqrt{5}}+\sqrt[3]{2-\sqrt{5}})\\x^3=4+3\cdot(-1)\cdot(x)$$so $$x^3+3x-4=0 \\(x-1)(x^2+x+4)\to\\ x=1,x^2+x+4=0 ,\Delta <0\\x=1$$

$\endgroup$
6
$\begingroup$

By observing that $$\left(\frac12\pm\frac{\sqrt 5}{2}\right)^3=\frac18\pm\frac{3\sqrt 5}8+\frac{15}{8}\pm\frac{5\sqrt 5}{8}=2\pm\sqrt 5$$ It follows $$\sqrt[3]{2+\sqrt 5}+\sqrt[3]{2-\sqrt 5}=\tfrac12+\tfrac{\sqrt 5}{2}+\tfrac12-\tfrac{\sqrt 5}2=1$$

$\endgroup$
  • $\begingroup$ Angel: how did you figure out the values $1/2$ and $1/2 \sqrt{5}$? $\endgroup$ – bluemaster Aug 16 '17 at 3:30
  • $\begingroup$ I have seen a similar problem before, and this was the only way that worked for me. I was looking for a pattern easy to compute and I got this one. $\endgroup$ – Ángel Mario Gallegos Aug 16 '17 at 3:33
5
$\begingroup$

Let $a=\sqrt[3]{2+\sqrt{5}}, b=\sqrt[3]{2-\sqrt{5}}\,$, then:

$$\require{cancel} a^3+b^3 = 2+\cancel{\sqrt{5}} + 2-\cancel{\sqrt{5}} = 4 \\ ab = \sqrt[3]{(2+\sqrt{5})(2-\sqrt{5})} = \sqrt[3]{2^2 - 5} = -1 $$

From $\,(a+b)^3 = a^3+b^3+3ab(a+b)\,$ and given that $\,x=a+b\,$ it follows that $\,x^3=4-3x\,$ $\iff 0 = x^3+3x-4=(x-1)(x^2+x+4)\,$, where only the first factor has a real root.

$\endgroup$
4
$\begingroup$

You can solve these types of problems by denesting each radical and then simplifying the terms that cancel out. In general, we have$$\sqrt[n]{A+B\sqrt[m]C}=a+b\sqrt[m]{C}$$From which you raise both sides to the nth power and expand using Newton's binomial theorem.


In this case, we have$$\sqrt[3]{2\pm\sqrt5}=a\pm b\sqrt5$$ Cubing both sides, and simplifying, we get the following systems of equations$$\begin{cases}a^3+15ab^2=2\\\\3a^2b+5b^3=1\end{cases}$$ Cross multiplying, and dividing both sides by $b^3$, we get a cubic in $\tfrac ab$. With a rational root at $a/b=1$. Therefore, we see that $a=b$ and$$a^3+15a^3=2\iff 16a^3=2\iff a=b=\frac 12$$Therefore, your radical simplifies into$$\sqrt[3]{2\pm\sqrt5}=\frac 12\pm\frac {\sqrt5}2$$And I will leave the rest of the problem for the OP to finish.

$\endgroup$
3
$\begingroup$

If you don't have to prove that $x \in \mathbb Z$, then it's easy:

$\hphantom-1 < 2+\sqrt{5} < 5 \implies \hphantom-1 < \sqrt[3]{2+\sqrt{5}} < 2$

$-1 < 2-\sqrt{5} < 0 \implies -1 < \sqrt[3]{2+\sqrt{5}} < 0$

Therefore, $ 0 < x < 2 $ and so $x=1$.

$\endgroup$
2
$\begingroup$

If you know the cubic formula for solving $$x^3 + px + q = 0$$ that helps. The formula is $$x = \sqrt[3]{-\frac{q}{2}+\sqrt{\frac{q^2}{4}+\frac{p^3}{27}}}+\sqrt[3]{-\frac{q}{2}-\sqrt{\frac{q^2}{4}+\frac{p^3}{27}}}$$ Given the "$2$"s in your expression, you might be led to consider $q=-4$, so the cubic $x^3 + px -4 = 0$ with solution $$x = \sqrt[3]{2+\sqrt{4+\frac{p^3}{27}}}+\sqrt[3]{2-\sqrt{4+\frac{p^3}{27}}}$$ Now it's clear that $p=3$ gives your expression. So your expression is a solution to $$x^3+3x-4=0$$ which factors as $$(x-1)(x^2+x+4)=0$$ The quadratic factor has no real roots. So your number must be $1$.

$\endgroup$
2
$\begingroup$

We can use $a^3+b^3+c^3-3abc=(a+b+c)(a^2+b^2+c^2-ab-ac-bc)$.

Since $a^2+b^2+c^2-ab-ac-bc=\frac{1}{2}((a-b)^2+(a-c)^2+(b-c)^2)$, we see that

$$a^2+b^2+c^2-ab-ac-bc=0\Leftrightarrow a=b=c.$$ Thus, since $\sqrt[3]{2+\sqrt5}\neq\sqrt[3]{2-\sqrt5}$, we obtaion $$x=\sqrt[3]{2+\sqrt5}+\sqrt[3]{2-\sqrt5}$$ it's $$x-\sqrt[3]{2+\sqrt5}-\sqrt[3]{2-\sqrt5}=0$$ or $$x^3-2-\sqrt5-2+\sqrt5-3x\sqrt[3]{(2+\sqrt5)(2-\sqrt5)}=0$$ or $$x^3+3x-4=0$$ or $$x^3-x^2+x^2-x+4x-4=0$$ or $$(x-1)(x^2+x+4)=0$$ or $$x=1.$$

We can make also the following. $$\sqrt[3]{2+\sqrt5}+\sqrt[3]{2-\sqrt5}=\frac{1}{2}\left(\sqrt[3]{16+8\sqrt5}+\sqrt[3]{16-8\sqrt5}\right)=$$ $$=\frac{1}{2}\left(\sqrt[3]{1+3\sqrt5+3\cdot5+5\sqrt5}+\sqrt[3]{1-3\sqrt5+3\cdot5-5\sqrt5}\right)=$$ $$=\frac{1}{2}\left(1+\sqrt5+1-\sqrt5\right)=1.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.